Fatores explicativos da evidenciação de informações ambientais das empresas potencialmente poluidoras listadas na BM&FBOVESPA - Santos, Lívia Maria da Silva (2016)
The present research aims to identify the determinants of environmental disclosure of potentially polluting companies listed on BM&FBOVESPA. To do so, the Standardized Financial Statements (DFPs), Reference Forms, Annual and Sustainability Reports of these companies were used in the period from 2005 to 2015. The research sample is formed by all publicly traded companies with shares traded on the BM&FBOVESPA, and belonging to the sectors of high, medium and low polluting potential, according to Law nº 10.165/2000, which deals with the National Environmental Policy. Based on the theories of Legitimacy and Stakeholders, and previous studies, twelve hypotheses were formulated about the possible determinants of environmental disclosure, with the variable regulated sectors being excluded from the model due to problems of multicollinearity, and the variable regulated companies was omitted For remaining fixed throughout the studied period. From the use of content analysis, to examine the evidence of environmental information and the application of the regression model with unbalanced panel data, of fixed effects with robustness, it was possible to reject or reject the research hypotheses. The results show, at a level of significance of 1% and 5%, that company size, profitability, internationalization and sustainability report are determining factors for the disclosure of environmental information. Although the indebtedness presented an inverse relation with the dependent variable, it was verified that this variable also explains the environmental evidence. On the other hand, auditing, board size, board independence, shareholder dispersion and sustainability are not relevant factors to explain environmental disclosure. Thus, of the twelve hypotheses, 4 were not rejected and 6 were rejected. These results are consistent with those of some national and international research, and are in accordance with the theories of Legitimacy and Stakeholders. This study aims to contribute to the knowledge of accounting science, regarding environmental disclosure, filling some gaps in this area and adding results to the existing literature.